Technical complications with tooth-supported fixed dental prostheses (FDPs) of different span lengths: an up to 15-year retrospective study - Ali Alenezi; Sarah Aloqayli (BMC, 2023)
Abstract Backgrounds Long-span dental bridges may cause excessive load on abutment teeth and the periodontal area, which may lead to bridge fractures or periodontal problems. However, some reports have revealed that short- and long-span bridges can provide a similar prognosis. This clinical study aimed to investigate the technical complications associated with fixed dental prostheses (FDPs) of different span lengths. Methods All patients with previously cemented FDPs were clinically examined during their follow-up visits. Several data related to FDPs were registered, such as design, material type, location, and type of complication. The main clinical factors analyzed were technical complications. Life table survival analyses were performed to calculate the cumulative survival rate of FDPs when technical complications were detected. Results The study examined 229 patients with a total number of 258 prostheses and an average of 98 months of follow-up. Seventy-four prostheses suffered from technical complications, and the most common complication was ceramic fracture or chipping (n = 66), while loss of retention occurred in 11 prostheses. The long-term evaluation of long-span prostheses revealed a significantly higher technical complication rate compared to short-span prostheses (P = ,003). The cumulative survival rate for short-span FDPs was 91% in year 5, 68% in year 10, and 34% in year 15. For long-span FDPs, the cumulative survival rate was 85% in year 5, 50% in year 10, and 18% in year 15. Conclusion Long-span prostheses (5 units or more) can be associated with a higher technical complication rate compared to short-span prostheses after long-term evaluation.